Identification of Novel Sources of Resistance to Seed Weevils (Bruchus spp.) in a Faba Bean Germplasm Collection - Carrillo-Perdomo, Estefanía; Raffiot, Blandine; Ollivier, Damien; Deulvot, Chrystel; Magnin-Robert, Jean-Bernard; Tayeh, Nadim; Marget, Pascal (Frontiers in Plant Science, 2019)
Seed weevils (Bruchus spp.) are major pests of faba bean, causing yield losses and affecting marketability. Our objective was to identify stable sources of resistance to seed weevil attacks, determine the climatic factors that most influenced its incidence and its relationship with some phenological and agronomic traits. The accessions “BOBICK ROD115”, “CÔTE D’OR”, “221516” and “NOVA GRADISKA” showed increased resistance to penetration and development of larvae. Other accessions such as “QUASAR”, “109.669” and “223303” exhibited resistance to larval development. The results of this work suggest the presence of different defense mechanisms to seed weevils in faba bean, which in the future could be introgressed in elite cultivars to create resistant varieties and contribute to more sustainable agriculture with less need for pesticides. The temperature, rainfall and humidity seemed to be the climatic factors most influencing faba bean seed weevil attack while earliness and small seed weight were correlated with less infestation rates in the different experiments.